The Relationship between the State and the Church in Education and Foreign Policy in the First Czechoslovak Republic - Baar, Vojtěch Lubomír (Civilia, 2022)
This paper aims to provide a comprehensive overview of events in the newly established Czechoslovak state in the field of education and the relationship between the state and the Catholic Church. It is an academic study drawing on contemporary journals, speeches by statesmen and official bilateral documents. It outlines new contexts and brings the context of the everydayness into a situation that is perceived as primarily political. The authors' observations from the school environment are then complemented by the reception of the Small Education Act (Malý školský zákon), which introduced compulsory subjects in Czechoslovak schools, one of which is civics. An evaluation of the impact of this law's implementation is offered.
Keywords: Secularism in Education; The Marmaggi Affair; The Small Education Act